Western flanks of the Central Asian late paleozoic continental rift system and uranium mineralization - S. A. Malyutin (Известия высших учебных заведений: Геология и разведка)
Introduction. Available information on the occurrences of high alkaline magmatic rocks fixing the position of the western flanks of the southern branches (Gobi Altai and Gobi Tien-Shan) of the Central Asian Late Paleozoic continental rift system in the territory of the North-West of Chingiz (the eastern part of Central Kazakhstan), the Kendyktas-Chu-Ili-Bet-Pak-Dal uranium-bearing province of the Southern Kazakhstan and the Chatkal-Naryn zone of Tien-Shan (Uzbekistan) is reviewed. Data on the confinement of uranium mineralization to these occurrences and its paragenetic relationship with the Late Paleozoic alkaline volcanic-plutonic association is provided.Aim. To study the uranium mineralization of Late Paleozoic alkaline magmatism to clarify metallogenic representations and justify prospects for the ore-bearingness of the western flanks of the southern branches of the Central Asian continental rift system.Materials and methods. The largest part of materials was obtained in the process of geological surveys and prospecting works of various scales in the regions of Central Kazakhstan in the period 1965–1985 with the participation of the author. Published materials concerning the subdivision of magmatic formations in the uranium ore fields of Southern Kazakhstan and the Chatkal-Naryn zone were also used.Results. Subvolcanic bodies of comendites and small masses of alkaline granites of the Late Paleozoic were identified across the area of uranium ore occurrences in the South-Western Chingiz and some deposits of South Kazakhstan confined to Devonian volcanic structures, which indicates their relationship with the southern branches of the Central Asian continental rift system. Rare-metalalbite, uranium-phosphorus and uranium-molybdenum formations are confined to alkaline rocks. Rare-metal mineralization is closely associated with alkaline rocks, while uranium mineralization occurred after the introduction of the most recent microgabbrodiorite and lamprophyre dikes. Similar correlations of rare-metal and uranium mineralization with alkaline granites and of microgabbrodiorite and lamprophyre dikes are observed in the uranium deposits of the Chatkal-Naryn zone located among the early Permian bimodal trachybasalt-trachyolite formation.Conclusion. The establishment of ore mineralization on the western flanks of the Gobi Altai and Gobi Tien-Shan branches in the territory of Southern and Central Kazakhstan allows these areas to be distinguished as metallogenic zones, promising in terms of rare-metal and uranium mineralization.